Economic Value of Cultural and Natural Heritage in Indonesia: A Case Study of Borobudur Temple Tourism - Sri Walyoto; Mudofir Mudofir; Jasanta Peranginangin (SHAHIH: Journal of Islamicate Multidisciplinary, 2019)
This study aims to construct a model for enhancing visitors' willingness to pay at tourist destinations, specifically in the case of Borobudur Temple. This research addresses a gap in the economic valuation of non-market goods or services, such as cultural heritage, which are often overlooked in conventional market mechanisms. The method employed is quantitative research using Structural Equation Modeling (SEM) with Borobudur Temple visitors as the research object. Data were collected using purposive sampling from 232 valid respondents through a structured questionnaire. Five hypotheses were developed to examine the relationships between perceived price, destination uniqueness, perceived cosiness, and willingness to pay. Model testing results using IBM SPSS AMOS 22 indicate that four hypotheses are significant, while one hypothesis is not significant. The main findings reveal that perceived price does not have a direct effect on willingness to pay but has a significant influence mediated by visitor cosiness. Destination uniqueness proves to be a crucial factor enhancing both cosiness and willingness to pay. This study contributes to formulating managerial strategies for cultural heritage tourism managers to optimize revenue through enhancing comfort and highlighting destination uniqueness, rather than merely adjusting prices.